HUBUNGAN TINGKAT PENDIDIKAN DENGAN PENGETAHUAN IBU TERHADAP PEMERIKSAAN PAP SMEAR DI WILAYAH KELUARGA BINAAN KESEHATAN FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ANGKATAN 2016 DI KECAMATAN MEDAN JOHOR SUMATERA UTARA TAHUN 2019 - CYNTHIA IRWANDA SARI; HEPPY JELITA SARI (JURNAL ILMIAH KOHESI, 2021)
Papanicolaou Test or pap smear is a gynecological screening method. First performed by Georgis Papanikolau to discover aprocess of premalignant or malignancies in the ectocervix or the outside of the cervix and infection in endocervix or theinside of the endometrium. Early detection of cervical cancer in Indonesia is very low. The pap smear examination isinfluenced by the level of education and knowledge. To find out the Relationship of Education Level with Mother's Knowledgeof Pap Smear Examination in the Health Fostered Family Area of the Faculty of Medicine, University of Muhammadiyah,North Sumatra 2016 Force in Medan Johor District, North Sumatra in 2019. This research method is descriptive analytic withcross sectional design and the data was collected by a total sampling technique. Forty-five mothers and respondents with anelementary education level and knowledge level of less than 19 people (100%). respondents with secondary education leveland secondary knowledge level of 20 people (100%). respondents with a high level of education and a good level ofknowledge are 6 people (100%). From the analysis data obtained P = 0,000 (P <0.05) this is related to the relationshipbetween the level of education with the mother's knowledge of the pap smear examination. The mother’s level of educationand knowledge can help with pap smear examination.